Successful collection and transplantation of peripheral blood stem cells in cancer patients using large-volume leukaphereses - Martin, Simona; Goldschmidt, Hartmut; Hahn, Uwe; Pförsich, Margit; Moos, Marion; Haas, Rainer (Journal of clinical apheresis, 1996)
It was the aim of our study to determine the collection efficiency and yield of CD34+ cells in 88 cancer patients (pts, 44 males/44 females) who underwent 154 large-volume leukaphereses (LV-LPs). The diagnoses were as follows: 18 patients had Non-Hodgkin's lymphoma, 9 Hodgkin's disease, 24 multiple myeloma, 6 acute leukemia, 27 breast cancer, and 4 patients had solid tumors of different types. During the course of LV-LPs, 20 liters (l) of blood were processed at a median flow-rate of 85 ml/min (CS 3000 Baxter) and 130 ml/min (COBE Spectra), respectively. Peripheral blood stem cells (PBSC) were collected following granulocyte colony-stimulating factor (G-CSF)-supported cytotoxic chemotherapy. A 31% and 21% mean decrease in the platelet and white blood count was noted at the end of the LV-LPs when compared with the pre-leukapheresis values. The aphereses were well tolerated without adverse effects. The level of circulating CD34+ cells was closely related to the number of CD34+ cells contained in the respective leukapheresis product (R = 0.89, P < 0.001). Compared with 270 patients who underwent 838 regular 101 LPs, the yield of CD34+ cells/kg was almost two-fold greater (4.84 ± 0.63 × 106 [Mean ± SEM] vs 2.60 ± 0.16 × 106, P < 0.001). The antigenic profile of CD34+ cells was assessed in 54 separate products collected on the occasion of 27 LV-LPs following the processing of 101 and 201, respectively. The intra-individual comparison included differentiation as well as lineage-associated markers (CD38, Thy-1, c-kit, CD33, CD45RA). No difference in the subset composition was observed between the first and second product, arguing against a preferential release of particular CD34+ cell subsets during the procedure. As shown by molecular biological or immunocytochemical examination, the likelihood of harvesting malignant cells using large-volume aphereses was not increased in comparison with regular leukaphereses. Single harvests of ≥2.5 × 106 CD34+ cells/kg could be obtained in 74% of the patients, compared with 52% in case of regular LPs. As the majority of patients were autografted with more than 2.5 × 106 CD34+ cells/kg following high-dose therapy, hematological recovery in general was rapid and not related to the type of apheresis product used. Considering patient comfort and savings in resource utilization, large-volume leukaphereses have become the standard procedure for PBSC collection in our center. © 1996 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 7. Dezember 1998
Gesehen am 23.04.2025